The Making of Tourism Film as an Instagramable Promotion Media in Harian Boho District, Samosir District - Samerdanta Sinulingga (Budapest International Research and Critics University, 2021)
Technology development has a major role in tourism growth in Indonesia. One of these technology products is Instagram. Instagram has been recognized worldwide as a platform that can give dominant influence on increasing product sales and increasing tourist visits to a tourism destination. This Instagram has 3 main content as a channel of information to society, namely video content, photos and written content. This is what wants to be tested experimentally in the Lake Toba region, especially in the Samosir Regency, the Harian Boho District. The initiation of this research was carried out not only as a copyright work, but through this research it can be understood the effectiveness of using films for promotional purposes on Instagram on its impact in increasing tourist visits to a tourism destination during the COVID-19 pandemic. The method that is used in this research is descriptive qualitative phenomenology with data collection techniques, namely snowball sampling. The results of this study found that publishing travel promotion films through social media Instagram turned out to have a very significant impact in increasing tourist visits to a destination. It was recorded that after publishing the film, the increase in tourist visits reached 1,648 visits (August 2020) even though in the previous month there were only 22 people recorded. From this experiment, it is proof that Tourism Promotion Films have significant influence on increasing tourist visits during the COVID-19 pandemic.